Clinical impact of serial change in brain natriuretic peptide before and after catheter ablation in patients with atrial fibrillation and heart failure. Issue 5 (May 2021) - Kuroda, Shunsuke; Mizukami, Akira; Hiroki, Jiro; Shimizu, Yuki; Arai, Hirofumi; Yamashita, Shu; Goya, Masahiko; Sasano, Tetsuo; Matsumura, Akihiko
Highlights: We examined cases with heart failure undergoing atrial fibrillation (AF) ablation. Brain natriuretic peptide (BNP) levels declined with wide range of its values after procedures. Reduction of BNP predicted prognosis in patients presenting with AF at baseline. Serial evaluation of BNP pre- and post-ablation might help in risk stratification. Abstract: Background: Brain natriuretic peptide (BNP) predicts the prognosis in patients with atrial fibrillation (AF) and heart failure (HF); however, the level of BNP can change immediately after restoration of sinus rhythm. We aimed to investigate the clinical impact of serial change in BNP level before and after catheter ablation for AF, on the prognosis. Methods: In this retrospective single center study, 162 consecutive patients (67±9 years, 66.7% male) with AF and concomitant HF who underwent catheter ablation were examined. We analyzed the cardiac rhythm and % change in BNP pre- and post-ablation. Results: BNP increased by 32.7% (-4.5% to 51.3%) in patients with sinus rhythm at baseline (sinus rhythm group: N=50) and decreased by 47.6% (20.9 to 61.6%) in patients with AF rhythm at baseline. Patients with AF rhythm at baseline were categorized into two groups according to the median value of reduction in % BNP; patients with good % BNP reduction (good BNP-R group; N=56), and with poor % BNP reduction (poor BNP-R group; N=56). Although the rate of recurrence of AF after ablation was comparable between the good and poor BNP-R groups, poor BNP-R was an independent predictor of subsequent composite events including HF hospitalization, ischemic stroke, and all cause of death after ablation, even after adjusting for other confounders (hazard ratio: 6.85, 95% confidence interval: 2.16 to 21.7, p -value=0.001). In the longitudinal analysis of echocardiographic parameters, shortening of the left ventricular end-diastolic diameter with preserved ejection fraction was evident except in the poor BNP-R group. Conclusion: In patients with AF and HF, poor % BNP reduction was an independent predictor of adverse outcome, although the rate of recurrence of AF was comparable. Serial BNP measurement might help in better identification of high-risk patients in whom sinus rhythm is restored with catheter ablation.